Karakteristik Tes Sakarin pada Rhinosinusitis Kronik di RSUD dr. Saiful Anwar, Malang January – December 2023 - Maharani, Iriana; Tallane, Sarah Tamania (Oto Rhino Laryngologica Indonesiana, 2025)
Background: The mucociliary system is the main defense mechanism in the respiratory tract as a protector from various particles, including bacteria. The mucociliary system will cause germs that enter to be expelled by coughing or swallowing. This system is greatly affected by many factors, such as respiratory tract infections, inflammation (rhinosinusitis), smoking habits, and pollutants. If the mucociliary system is not in good condition, the clearance time will be prolonged. Evaluation method to determine the function of the mucociliary system is the saccharin test, which is non-invasive, easily reproducible, low cost, and does not require special expertise to perform. Purpose: To know the timing of the saccharin test in chronic rhinosinusitis (CRS) patient. Method: Observational descriptive study with a cross-sectional design to find the timing of the saccharin test in CRS at ENT Department Dr. Saiful Anwar General Hospital from January-December 2023. Result: The most common finding was normal saccharin time in 46 patients (90%), and prolonged saccharin time in 5 patients (12%). The average saccharin time in chronic rhinosinusitis patients is 7.5±5.9. Most of patients were chronic rhinosinusitis without polyp (81%) with average saccharin test were 7.1±5.87, and majority were both non polyp and non-allergic rhinitis (43%) with average 8.2±6.1. Conclusion: Saccharin test could be abnormal in chronic rhinosinusitis, but overall patients with chronic rhinosinusitis had a normal average saccharin time, on both polyp and non-polyp rhinosinusitis. The results also showed that the saccharin test time was longer in chronic rhinosinusitis with polyps.